Demyristoylation of the Cytoplasmic Redox Protein Trx-h2 Is Critical for Inducing a Rapid Cold Stress Response in Plants - Eun Seon Lee; Joung Hun Park; Seong Dong Wi; Ho Byoung Chae; Seol Ki Paeng; Su Bin Bae; Kieu Anh Thi Phan; Min Gab Kim; Sang-Soo Kwak; Woe-Yeon Kim; Dae-Jin Yun; Sang Yeol Lee (Antioxidants, 2021)
In Arabidopsis, the cytosolic redox protein thioredoxin h2 (Trx-h2) is anchored to the cytoplasmic endomembrane through the myristoylated second glycine residue (Gly2). However, under cold stress, the cytosolic Trx-h2 is rapidly translocated to the nucleus, where it interacts with and reduces the cold-responsive C-repeat-binding factors (CBFs), thus activating cold-responsive (COR) genes. In this study, we investigated the significance of fatty acid modification of Trx-h2 under cold conditions by generating transgenic Arabidopsis lines in the trx-h2 mutant background, overexpressing Trx-h2 (Trx-h2OE/trx-h2) and its point mutation variant Trx-h2(G/A) [Trx-h2(G/A)OE/trx-h2], in which the Gly2 was replaced by alanine (Ala). Due to the lack of Gly2, Trx-h2(G/A) was incapable of myristoylation, and a part of Trx-h2(G/A) localized to the nucleus even under warm temperature. As no time is spent on the demyristoylation and subsequent nuclear translocation of Trx-h2(G/A) under a cold snap, the ability of Trx-h2(G/A) to protect plants from cold stress was greater than that of Trx-h2. Additionally, COR genes were up-regulated earlier in Trx-h2(G/A)2OE/trx-h2 plants than in Trx-h2OE/trx-h2 plants under cold stress. Consequently, Trx-h2(G/A)2OE/trx-h2 plants showed greater cold tolerance than Col-0 (wild type) and Trx-h2OE/trx-h2 plants. Overall, our results clearly demonstrate the significance of the demyristoylation of Trx-h2 in enhancing plant cold/freezing tolerance.